PENELITIAN TINDAKAN KELAS - Noor Azida Batubara; Maskupah Maskupah; Rida Tusyifa; Siti Khoerunnisa; Wilda Umayyah (JURNAL ILMIAH NUSANTARA, 2026)
This classroom action research aims to address learning problems characterized by low student achievement, limited participation, and the presence of misconceptions in understanding the subject matter. The problems were identified through a clear gap between the ideal learning conditions and the actual classroom situation, supported by initial data such as students’ scores below the minimum mastery criteria (KKM), low engagement during discussions, and recurring conceptual errors. The study is grounded in constructivist, behaviorist, and cooperative learning theories, which guided the design of improvement strategies, including active learning methods, group discussions, visual media, and interactive activities. The research was conducted in two cycles following the spiral model consisting of planning, action, observation, and reflection. Data were collected through learning achievement tests, observation sheets, field notes, interviews, and visual documentation. Both quantitative and qualitative analyses were employed. The results showed a significant improvement in students’ participation and learning outcomes. The average score increased from 62 (pre-action) to 74 in Cycle I and 85 in Cycle II. Mastery learning improved from 40% to 90%, while student participation rose from 35% to 80%. These findings indicate that the implemented actions were effective in enhancing both the learning process and outcomes. The improvements align with theoretical principles related to social interaction, reinforcement, and knowledge construction through active learning. The study recommends maintaining the use of active learning strategies and suggests further research in different subjects or classroom contexts to enrich the findings.